2017
DOI: 10.1667/rr14563.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure Enhances Hepatocyte Proliferation in Neonatal Mice but not in Adult Mice

Abstract: There is a natural tendency to expect that irradiation of an infant organ prior to development-related expansion will result in a higher risk of developing cancer than that of fully-developed adult tissue, and this has generally been observed. However, if tissues also vary in their initial responses to radiation depending on age, the interplay between tissue- and age-dependent risk would potentially be quite complex. We have previously shown opposing age-dependent induction of apoptosis for the intestinal epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…We further examined cell proliferation in the liver of mice subjected to irradiation and CR. We previously reported that radiation exposure at an early stage of life does not induce apoptosis but rather increases hepatocyte proliferation, although mature hepatocytes generally undergo cell division only occasionally 14 . Consistent with this fact, Ki‐67 + hepatocytes were very rare in the normal liver tissue of our nonirradiated mice, and this was also the case in the fatty liver areas of mice in the 3.8 Gy‐65 kcal group.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…We further examined cell proliferation in the liver of mice subjected to irradiation and CR. We previously reported that radiation exposure at an early stage of life does not induce apoptosis but rather increases hepatocyte proliferation, although mature hepatocytes generally undergo cell division only occasionally 14 . Consistent with this fact, Ki‐67 + hepatocytes were very rare in the normal liver tissue of our nonirradiated mice, and this was also the case in the fatty liver areas of mice in the 3.8 Gy‐65 kcal group.…”
Section: Resultssupporting
confidence: 88%
“…10 Studies on the mechanism of radiation carcinogenesis have indicated that ionizing radiation can directly or indirectly induce DNA damage, epigenetic modifications, cellular senescence, genomic instability via dysfunctional telomeres, inflammatory responses and immune disorders, among other afflictions, each (or combinations) of which may lead to the development of cancer. [11][12][13] Our established mouse model of radiation tumorigenesis previously revealed that, in infant hepatocytes, although DNA double-strand breaks could be detected, the potential positive effects of a modest accumulation of p53 and p21-mediated cell-cycle arrest in a small fraction of damaged cells were overshadowed by further stimulation of proliferation in the neonatal liver over the hours and days following irradiation, 14 and an analysis of mutations in spleen cells also revealed that early-life radiation exposure led to greater mutation clonality. 15 However, although these findings indicated that irradiation contributes to tumor induction, most previous investigations have focused on short-term time points after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The data which are now being made available through J-SHARE have been used in a number of studies to date, reflecting the transition from retrospective entry of completed experiments into the archives towards real-time integration of our animal experiments and the recording of data directly into the J-SHARE platform. (Shang 2017, Yamada 2017, Showler 2017, Takabatake 2016, Tsuruoka 2016, Imaoka 2016, Morioka 2018.…”
Section: Digitisation Conversion and Translationmentioning
confidence: 99%
“…In experiments using mice, characteristics of radiation effects are dependent on ages, sex and strains [8,9,10,11,12]. In terms of age-dependency, radiation exposure in infancy, as the active, proliferative stage of liver development, appears related to carcinogenesis [11,23]. Moreover, radio-sensitivity leading to liver carcinogenesis appears to differ among mouse strains [8].…”
Section: Effects Of Radiation On the Livermentioning
confidence: 99%